2020
DOI: 10.1590/1678-4162-11767
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reproductive and animal welfare parameters of swine females of different genetic lines submitted to different reproductive management and housing systems during pregnancy

Abstract: The aim of this study was to evaluate swine females of different genetic lines submitted to different reproductive management and housing systems during pregnancy on reproductive performance and animal welfare parameters. After artificial insemination protocol, 524 females were divided into two gestation housing systems: PEN1=animals housed in individual stalls during the breeding and after group-housed; PEN32=animals housed in individual stalls from breeding until 32 days of pregnancy and after group-housed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Van der Mheen et al ( 2003) looked at 375 sows during 800 pregnancies and found the highest litter size in sows that were introduced (grouped) into dynamic groups immediately after insemination compared to sows introduced to dynamic groups at 2 or 4 weeks post-service. The majority of other studies show no effect of grouping time on litter size (Galli et al, under review;Kirkwood and Zanella, 2005;Li and Gonyou, 2013;Knox et al, 2014;Stevens et al, 2015;Cunha et al, 2018;Bampi et al, 2020). However, Knox et al (2014) reported lower pregnancy rates for sows grouped in early pregnancy (d3) compared to sows regrouped 14 or 35 days after service (the low space allowance in this study of 1.74 m 2 /sow should be noted).…”
Section: Effects On Reproductive Performance Of Grouping Sows In the ...mentioning
confidence: 51%
See 2 more Smart Citations
“…Van der Mheen et al ( 2003) looked at 375 sows during 800 pregnancies and found the highest litter size in sows that were introduced (grouped) into dynamic groups immediately after insemination compared to sows introduced to dynamic groups at 2 or 4 weeks post-service. The majority of other studies show no effect of grouping time on litter size (Galli et al, under review;Kirkwood and Zanella, 2005;Li and Gonyou, 2013;Knox et al, 2014;Stevens et al, 2015;Cunha et al, 2018;Bampi et al, 2020). However, Knox et al (2014) reported lower pregnancy rates for sows grouped in early pregnancy (d3) compared to sows regrouped 14 or 35 days after service (the low space allowance in this study of 1.74 m 2 /sow should be noted).…”
Section: Effects On Reproductive Performance Of Grouping Sows In the ...mentioning
confidence: 51%
“…Most of the studies show no effect on farrowing rate of grouping at 3 compared to 28 days postinsemination (van der Mheen et al, 2003;Kirkwood and Zanella, 2005;Stevens et al, 2015;Cunha et al, 2018;Bampi et al, 2020;Galli et al, under review). However, two studies reported lower farrowing rates for sows grouped very soon after insemination compared to sows grouped 4 weeks later (Li and Gonyou, 2013 [82.3 vs. 86.7%]; Knox et al, 2014 [82.8 vs. 90.5%]).…”
Section: Farrowing Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the use of auditory environmental enrichment, no effects of type of housing during gestation were observed on sow reproductive indices, which indicates that the collective housing system may be considered a viable alternative to reduce the time of individual confinement without compromising economic and performance results. Gentilini et al and Bampi et al, [ 32 , 33 ] found no differences in birth rates between the two housing systems, crates or collective pens. Mixed housing, in which sows are kept for about 28 to 35 days in individual crates after artificial insemination, mainly aims to avoid embryo losses, which is influenced by stress due to disputes to establish a social hierarchy or for food [ 9 ]; thus, fights related to social hierarchy may be observed in the first days of regrouping.…”
Section: Reproductive Indicesmentioning
confidence: 97%
“…Additionally, piglets exposed to music had a lower expression of agonistic behaviors and an increased expression of playful behaviors [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The expression of abnormal behaviors, such as stereotypies and excessive aggressiveness, indicate unfavorable welfare conditions [ 40 ], which are related to facility issues and improper animal management, resulting in a decrease in productive performance.…”
Section: Reproductive Indicesmentioning
confidence: 99%